Tinjauan Etis Teologis Ibadah Kuno Dibalik Kebudayaan Ritual Mahelur Masyarakat Kristen Minahasa Sulawesi Utara - Merry Regina Mamuko (MAGENANG : Jurnal Teologi dan Pendidikan Kristen, 2023)
This study discusses the theological ethical review of the Mahelur ritual practice behind the culture of the Minahasa Christian community of North Sulawesi. The research method used is qualitative with data collection techniques through observation, interviews, and documentation studies. This study aims to find the theological ethical meaning behind this ritual practice and provide conclusions that can be understood as follows: First, the Mahelur ritual practice is carried out to re-establish a relationship with God as the creator of the universe, where blessings will continue to flow in the life of the Minahasa people. Second, there are views pro and con against the practice of Minahasa cultural rituals, where views that reject and regard it as a misguided act are caused by a lack of understanding of the history and meaning of Minahasa culture. Third, the conclusion of this study shows that the Mahelur ritual practice basically has a theological ethical meaning that establishes and builds a relationship with the creator of the universe in order to be given blessings and abundance in human life. It teaches that the source of blessings, life, and success comes.